Analysis of Logistics Delivery Performance (A Case Study of Rental ToolsDelivery in “XYZ” Power Plant Project at The Energy Service Fossil Division) - RINALDI RAYMOND; NILA K. HIDAYAT; LINUS PASASA; EFRATA D. S. YUNUS (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
The purpose of this study is to analyze the logistics delivery performance of rental tools delivery for temporary import in XYZ Power Plant Project at the Energy Service Division. This research is a mixture of quantitative and qualitative research and using both primary and secondary data, which collected from the company data including interview with the logistics manager and monitoring delivery data of XYZ Power Plant Project in the Logistics Department Energy Service Division. After the data was gathered, AMOS software is used to provide Structural Equation Modeling (SEM) and Path Diagram in order to identify influential factors to logistics delivery performance. Furthermore, to measure the KPI in terms of delivery reliability of logistics delivery performance levels of rental tools in XYZ power plant project in 2013 by the logistics department in the energy service fossil division. This study uses time series data from September 2013 - December 2013. Based on the results of research, it can be seen that customs clearance has positive moderate correlation to the logistics delivery performance, while number of items factor has a positive weak correlation to the logistics delivery performance. This research also found that the KPI in terms of delivery reliability of delivery performance level of rental tools in XYZ power plant project 2013 by the logistics department in the energy service division is 56.67%” which is Insufficient in logistics benchmark level. Thus, in purpose of increasing the logistics delivery performance in the XYZ Power Plant Project, the company should improve the delivery reliability. In addition the company should pay more attention to customs clearance process, since customs clearance is the most influential factor to the logistics delivery performance.Keywords: Logistics, Delivery Reliability, KPI, Temporary Import, On-Time Delivery.